Increasing of Knowledge and Interest in Vertiminaponic Cultivation for Teenagers in Gelora Indah Mosque Orphanages, Purwokerto Lor: Peningkatan Pengetahuan dan Minat tentang Budidaya Vertiminaponik Remaja Panti Asuhan Masjid Gelora Indah Purwokerto Lor - Eka Oktaviani; Agus Suroto; Imastini Dinuriah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
An orphanage is a place of residence and care, both for orphans and for abandoned children. The Gelora Indah Mosque Orphanage in Purwokerto is inhabited by thirteen teenagers. The potential of the second floor attic of this orphanage has not been maximized. With the condition of the yard land that is not spacious and to equip the teenagers with soft skills, one technology that can be applied is the vertiminaponic technique. This technique combines plant cultivation (hydroponics) and fish (aquaculture) in one place/land that is arranged vertically. Community service activities are carried out using the lecture method followed by cultivation assistance. The results of community service show an increase in knowledge and concepts about vertiminaponic cultivation of the orphanage teenagers by 83.34% and 49.58%. Meanwhile, when viewed from the aspect of knowledge about equipment and stages in vertiminaponic cultivation, there is an increase of 65.26% and 70.32%. This activity is an initiation in order to increase food independence for the orphanage teenagers through diversification of processed products from cultivation.